Long‐term outcomes of patent foramen ovale closure or medical therapy after cryptogenic stroke: A meta‐analysis of randomized trials. Issue 1 (4th May 2018) - Abdelaziz, Hesham K.; Saad, Marwan; Abuomara, Hossamaldin Z.; Nairooz, Ramez; Pothineni, Naga Venkata K.; Madmani, Mohamed E.; Roberts, David H.; Mahmud, Ehtisham
Abstract: Objectives: To examine long‐term clinical outcomes with transcatheter patent foramen ovale (PFO) closure versus medical therapy alone in patients with cryptogenic stroke. Background: A long‐standing debate regarding the optimal approach for the management of patients with PFO after a cryptogenic stroke exists. Methods: An electronic search was performed for randomized clinical trials (RCTs) reporting clinical outcomes with PFO closure vs. medical therapy alone after stroke. Random effects DerSimonian‐Laird risk ratios (RR) were calculated. The main outcome was recurrence of stroke. Other outcomes included transient ischemic attack (TIA), new‐onset atrial fibrillation/flutter (AF/AFL), major bleeding, serious adverse events, and device‐related complications. All‐cause mortality was also examined. Results: Five RCTs with a total of 3, 440 patients were included. At a mean follow‐up of 4.02 ± 1.57 years, PFO closure was associated with less recurrence of stroke (RR = 0.43; 95% CI 0.19–0.91; P  = .027) compared with medical therapy alone. No difference was observed between both strategies for TIA ( P  = .21), major bleeding ( P  = .69), serious adverse events ( P  = .35), and all‐cause death ( P  = .48). However, PFO closure, was associated with increased new‐onset AF/AFL ( P  < .001), risk of pulmonary embolism ( P  = .04), and device‐related complications ( P  < .001). On a subgroup analysis, stroke recurrence rate remained lower in PFO closure arm regardless of the type of closure device used ( P interaction  = .50), or the presence of substantial shunt in the majority of study population ( P interaction  = .13). Conclusions: Transcatheter PFO closure reduces the recurrence of stroke compared with medical therapy alone, with no significant safety concerns. Close follow‐up of patients after PFO closure is recommended to detect new‐onset atrial arrhythmias.